Isolation, characterization, and antimicrobial resistance of Gram-negative aerobic and facultative anaerobic bacteria from soil samples - da Silva, Paulo (2005)
Gram-negative aerobic bacteria are found in nearly 7% of soil resident-bacteria population. Many bacteria species are pathogenic, and they are responsible for nosocomial infections. Antimicrobial drugs resistance is relevant for assessing the potential pathogenic features of circulating bacteria strains. The aim of the present study was to identify Gram-negative bacilli (GNB) isolated from soil,and to test the antimicrobial resistance. Eighteen soil samples were inoculated into Hajna's broth for enrichment. Bacterial isolation was done on Mc Conkey agar and Müeller Hinton blood agar. Isolated bacteria colonies (283) were inoculated onto modified Rugai medium for screening the fermentative GNB and non-fermentative GNB, and followed by identification by means of conventional methodology. Most of them (94. 35%) belonged to Enterobacteriaceae,and 5. 65% were non-fermentative GNB. High rates of bacterial resistance were evidenced to ampicillin, cefalotin, cefoxitin, amoxicillin+clavulanic acid, and tetracycline,varying from 49. 82% to 87. 28%. All of the isolated bacteria showed resistance to at least one antibiotic. These results provide remarkable data on pathogenic potential as a constituent of a resistance reservoir. Further studies on the relationship between soil and antimicrobial resistance needs to be performed. Then the advanced experiments and observations will provide best understanding on the mechanism and the process associated with the emergence of environmental drug-resistant bacteria.